2017
DOI: 10.4103/sni.sni_452_16
|View full text |Cite
|
Sign up to set email alerts
|

Nontraumatic, posterior circulation pseudoaneurysm of the basilar artery summit with complete spontaneous resolution: Case report and literature review

Abstract: Background:Intracranial pseudoaneurysms are rare vascular defects of arterial walls that are classically the result of traumatic injury, iatrogenic causes, or infection. Idiopathic pseudoaneurysms are seen even less frequently and are often related to atherosclerosis. Pseudoaneurysms are most commonly found along the distal wall of the internal carotid artery, however, can occur at any location in the cerebrovascular circulation. Treatment of these arterial defects is often challenging due to their frail natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The mechanism of spontaneous occlusion remains unclear. It may be due to vascular remodeling response to injury as well as spontaneous thrombus formation (84). Those studies suggest that some specific pseudoaneurysms may at least have a potentially benign course with conservative treatment.…”
Section: Conservative Treatmentmentioning
confidence: 98%
See 2 more Smart Citations
“…The mechanism of spontaneous occlusion remains unclear. It may be due to vascular remodeling response to injury as well as spontaneous thrombus formation (84). Those studies suggest that some specific pseudoaneurysms may at least have a potentially benign course with conservative treatment.…”
Section: Conservative Treatmentmentioning
confidence: 98%
“…Those studies suggest that some specific pseudoaneurysms may at least have a potentially benign course with conservative treatment. Observation might be considered in pseudoaneurysms with decreased size and flow in repeated conventional angiography compared with the initial images (84). However, a recent study reported an unusual course of a cerebral pseudoaneurysm (69).…”
Section: Conservative Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Pseudoaneurysms do not have a normal vascular wall structure and are prone to rebleeding, endangering the patient's life. [5,6] However, there are no similar reports in PubMed. Endovascular therapy is currently the best treatment for basilar artery fenestration with an aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…[3,4] This study reports the case of a patient with basilar artery fenestration deformity and an aneurysm at the mid-distal junction. While pseudoaneurysm formation could not be excluded, [5,6] it is very rare in the clinic. Currently, little is known about this condition, and relatively few data based on experience with interventional therapies are available.…”
Section: Introductionmentioning
confidence: 99%